Analisis Efektivitas Pelayanan Sertipikat Tanah pada Kantor Pertanahan Kabupaten Banyuasin - Feriadi Feriadi; Mega Nugraha; Sunarto Sunarto (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2024)
Feriadi. This study focuses on analyzing the effectiveness of land certificate services at the Land Office of Banyuasin Regency. The purpose of the study was to find out how much effective the land certificate service was at the Land Office of Banyuasin Regency. The theory of effectiveness uses the theory of Martani and Lubis (2012) where the service effectiveness parameters include efficiency in service, the spirit of cooperation and work group loyalty. service procedures, responsiveness of employees, facilities and infrastructure. The method used is descriptive method. qualitative.. The results showed that the land certificate service at the Land Office of Banyuasin Regency had been running quite effectively, but not yet optimally. This can be seen from the following indicators: 1. Efficiency in Service, in terms of cost and time. Service fees are in accordance with applicable regulations and there are no additional fees (extortion) charged to the community. However, in terms of time, namely the speed and timeliness of the service, it is felt by the community that it is not fast and precise, even though the employee has clearly and transparently informed about the standard time for completion of land certificate management.2. The Spirit of Cooperation and Loyalty of the Working Group, the Spirit of Cooperation in the Land Office of Banyuasin Regency both between the leadership and staff have a good cooperative relationship, the open nature of the leadership and subordinates increases the loyalty of the working group. A sense of working group loyalty that is instilled through the placement of employees in accordance with the educational background and expertise and discipline of employees in serving the community.3. The service procedure is clear but has not been implemented in accordance with the existing service mechanism, because there are still complaints from the public about the service process which is still convoluted and there are many administrative requirements. Responsiveness (responsiveness) of employees, has been maximal in responding to community complaints by being responsive, friendly and speaking politely and easily understood by the community which gives the impression of being a pleasant person. Facilities and infrastructure, the condition of the service room is clean, comfortable and gives a safe impression. While the availability of supporting facilities such as waiting rooms, TV, air conditioning, places of worship and parking lots are already there and adequate. The existence of media/information sources that can be easily and directly accessed by the public and an Online Service System (Website) is applied.